The Role of Big Data Analytics in Strategic Decision-Making in Modern Retail Case Study: Indomaret and Alfamart - Yusep Saepulloh (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Massive digital transformation has fundamentally changed the landscape of the modern retail sector, shifting the reliance on managerial intuition toward precise, fact-based decision-making. This analysis explores in depth how the integration of Big Data Analytics (BDA) supports the effectiveness of business strategies within two major retail players in Indonesia, namely Alfamart and Indomaret. Utilizing a descriptive qualitative approach with a case study method, the study was conducted by synergizing data from literature reviews, in-depth interviews, and digital observations of application ecosystems such as Alfagift and Klik Indomaret. The results of the analysis show that the implementation of BDA has a significant impact by increasing decision-making speed by 54%, reducing demand prediction error rates by 48.6%, and optimizing logistics efficiency by up to 18.2%. The utilization of the Apriori algorithm in Market Basket Analysis and the integration of AI into CRM systems have proven capable of revealing consumer behavior patterns to enable more accurate product bundling strategies and service personalization. Although offering a high competitive advantage, this implementation faces critical challenges, including a shortage of expert human resources, infrastructure readiness, and compliance obligations regarding the Personal Data Protection Act (UU PDP) Number 27 of 2022. Ultimately, the success of this digital transformation depends heavily on the formation of a data-driven organizational culture and transformational leadership.